Measurements of UV-A radiation and hazard limits from some types of outdoor lamps. (2nd December 2014) - El-Moghazy, E.; Abd-Elmageed, A.-E.A.; Reda, S.
Abstract : Illumination using artificial light sources is common in these days. Many manufactures are paying for the design of lamps depending on high efficacy and low UV hazards. This research is focusing on the most useable lamps in the Egyptian markets; high pressure mercury (HPM), metal Halide (MH), and high pressure sodium (HPS). A set up for relative spectral power distribution based on single monochromator and UVA silicon detector for absolute irradiance measurements are used. The absolute irradiance in (W/m 2 ) in UVA region of the lamps and their accompanied standard uncertainty are evaluated.